2017
DOI: 10.4236/ojog.2017.77078
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Outcomes and Prognosis Score in Obstetric Vesico-Vaginal Fistula Repair

Abstract: An estimated 2 million women living in countries with limited resources currently have vesico-vaginal, recto-vaginal, or mixed types of fistulae because of the necrosis that occurs with obstructed labor. We evaluated factors readily assessed by the examining practitioner in a consecutive case series of surgical repairs of obstetrical fistulae, for the ability of those factors to stand as a prognostic guide, in a clinical score. Objectives: To identify the predictors of surgical repair outcomes and establish a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Our postoperative success rates are slightly higher when compared with similar studies performed in the region 11–14 . The most comparable study to ours was conducted by Mubikayi et al 11 in the DRC and reported an overall 85.7% success rate for VVF repairs. Although the number of women included (n = 483), the sociodemographic variables, and geographical location of repair were all similar, the 10% lower postoperative success rate is most likely explained by several factors.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our postoperative success rates are slightly higher when compared with similar studies performed in the region 11–14 . The most comparable study to ours was conducted by Mubikayi et al 11 in the DRC and reported an overall 85.7% success rate for VVF repairs. Although the number of women included (n = 483), the sociodemographic variables, and geographical location of repair were all similar, the 10% lower postoperative success rate is most likely explained by several factors.…”
Section: Discussionsupporting
confidence: 60%
“…Generally, it can be expected that midvaginal VVF will have better postoperative outcomes when compared with juxtacervical VVF, owing mostly to their superior accessibility 10 . Our postoperative success rates are slightly higher when compared with similar studies performed in the region 11–14 . The most comparable study to ours was conducted by Mubikayi et al 11 in the DRC and reported an overall 85.7% success rate for VVF repairs.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This finding was higher than other studies conducted in different study areas like: Democratic Republic of the Congo (24%), Guinea (14.5%), Zambia (27.1%), Yirgalem of Ethiopia (18.3%). 2,13,20,21 The reason for the higher rate of repair failure might be because of the differences in diagnostic accuracy, evaluation and timely repair using procedures that exploit basic surgical principles and the application of interposition flaps. 22,23 Weight of women during repairing was the factor for OF repair failure.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also supported by other studies in different areas. 20,21,28 Among fistula repairing women who developed postoperative infection were almost 3 times more likely to experience fistula repairing failure than their counterparts. This finding was in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%